Phlogopite-Olivine Nephelinites Erupted During Early Stage Rifting, North Tanzanian Divergence - Baudouin, Céline; Parat, Fleurice (Frontiers in Earth Science, 2020)
The North Tanzanian Divergence (NTD, eastern branch of the East African Rift) corresponds to an early stage of continental breakup. In the southern NTD, two quaternary volcanoes of the Manyara-Balangida rift (Labait, Kwaraha) have erupted primary nephelinite lavas (Mg# = 79–57) that allow characterization of their deep mantle source and the alkaline magmas that percolated through the lithosphere during rift initiation. Nephelinites are olivine- and clinopyroxene-rich, and contain up to 4 vol% magmatic phlogopite that crystallized as a liquidus phase with olivine and clinopyroxene. The presence of hydrous mineral (phlogopite) phenocrysts in Kwaraha and Labait lavas strongly suggests that the alkaline melts were H2O-bearing at the time of phlogopite crystallization (1.57–2.12 wt% H2O in phlogopite), demonstrating that phlogopite may have influenced the partitioning of water between the silicate melt and anhydrous silicate minerals (<1 ppm wt H2O clinopyroxene, 1–6 ppm wt H2O in olivine). Geochemical modeling indicates that the nephelinite magmas resulted from a low degree of partial melting (0.2–1%) of a carbonate-rich (0.3%) garnet peridotite containing ∼2 vol% phlogopite. We estimate the depth of partial melting based on primary melt compositions and empirical relations, and suggest that melting occurred at depths of 110–130 km (4 GPa) for craton-edge lavas (Kwaraha volcano) and 150 km (5 GPa) for on-craton lavas (Labait volcano), close to or below the lithosphere-asthenosphere boundary in agreement with the presence of deep refractory mantle xenoliths in Labait lavas. The depth of melting becomes gradually deeper toward the southern NTD: highly alkaline magmas in the north (Engaruka-Natron Basin) are sourced from amphibole- and CO2-rich peridotite at 75–90 km depth, whereas magmatism in the south (south Manyara Basin) is sourced from deep phlogopite- and CO2-rich garnet-peridotite beneath the Tanzania craton (e.g., at the on-craton Labait volcano). Percolation of deep asthenospheric CO2-rich alkaline magmas during their ascent may have produced strong heterogeneities in the thick sub-continental lithospheric mantle by inducing metasomatism and phlogopite crystallization in glimmerite lithologies.